Regional Cultural Differences, Financial Structure and Economic Growth Efficiency: Theory and Chinese Experience - GUO , YATING; Rosland , Anitha; Ishak , Suryati; Senan, Mohamad Khair Afham Muhamad (Journal of Ecohumanism, 2025)
Against the backdrop of profound changes in the global economic landscape and intensifying regional development imbalances, exploring the impact of regional cultural differences on the evolution of financial structure and economic growth efficiency has important theoretical value and practical significance for promoting regional coordinated development and high-quality economic transformation. Based on the theory of institutional embeddedness and financial development theory, this study constructs a theoretical analysis framework that includes cultural differences, financial structure and economic growth efficiency. Using China's provincial panel data from 2000 to 2023 and adopting spatial econometric methods, this paper systematically examines the transmission mechanism by which regional cultural differences affect economic growth efficiency by influencing the choice of financial structure. The study found that: first, regional cultural differences significantly affect the marketization degree of financial structure, and regions with stronger risk aversion tendencies are more dependent on bank-dominated financial structures; second, there is a significant spatial spillover effect between financial structure and economic growth efficiency, and a financial structure with a higher degree of marketization helps to improve regional economic growth efficiency; third, regional cultural differences have an indirect effect on economic growth efficiency by influencing the choice of financial structure, and this effect shows significant heterogeneity at different stages of regional development. This study provides new theoretical perspectives and policy implications for deepening financial supply-side structural reform and promoting regional coordinated development.